Semiotics of traditional Kazakh food - Gulzhan Artykbayeva, Zukhra Ismagambetova, Anar Uyzbayeva, Saltanat Aubakirova, Mayra Kozhamzharova, (Opción, 2019)
In this article, the authors consider the symbolic aspects of one of the rituals of Kazakh food – the sybaga (share, portion), which is an important component of Kazakh household culture. The methodological basis was laid in the works of foreign researchers, as well as scientific works of Kazakhstani scientists. As a result, according to the custom, the hosts serve treatment in special dishes - tabak (tray). In conclusion, in modern conditions of standardization and unification of many cultural and everyday phenomena, the sphere of food prohibitions and priorities preserves the maximum number of ethnically significant features.